Comprehensive Single-Cell RNA Sequencing Analysis of Cervical Cancer: Insights Into Tumor Microenvironment and Gene Expression Dynamics - Xiaoting Shen; Huier Sun; Shanshan Zhang (International Journal of Genomics)
Conclusion: Our large scale scRNA-seq of cervical cancer provide insights into cellular heterogeneity and gene expression dynamics within the tumor microenvironment.